Statistical methods in grape and wine research for quantifying the impact of climate change - German Puga; Kym Anderson (OENO One)
Studies analysing the impact that climate change could have on the wine sector are important for determining appropriate adaptation strategies. Statistical methods provide a useful approach for estimating future climate impacts. Yet they are underused despite the availability of data and the low costs of using statistical models when compared to some other approaches. This review aims to explain how some statistical methods can be used to quantify the impact of climate change in grape and wine research. It first focuses on how to estimate appropriate models of the impact of climate or weather on wine-related outputs. It then explains the challenges of using those statistical estimates to predict the impact of climate change. Last, the review compares statistical methods with other approaches and justifies combining different methods as a way of devising more insights for the wine sector.